The Relationship of Emotional Intelligence and Self Esteem with Self-Efficacy in College Students - Hany Fatikasari; M. Martono Diel; Ida Farida (Jurnal Vocational Nursing Sciences (VNUS), 2023)
Background : Self efficacy It is very important to fulfill life's obligations, until results are achieved. Emotional intelligence is the ability to recognize our own feelings and the feelings of others, the ability to motivate ourselves, and the ability to manage emotions well. Self esteem the higher the higherself efficacy career decision making.Research purposes :to find out the relationship between emotional intelligence andself esteem withself efficacy on Yatsi Madani University students. Research methods :This research uses quantitative methodscross sectional, plansnon probability sampling dno onerandom sampling, population 699 respondents. Number of samplesfall down5% of 118 respondents.Research result:It is known that 120 respondents were 70 respondents (58.3%) medium, 43 respondents (35.8%), high 16 respondents (13.3%) low, using the testchi-square, markp-value 0.004 < 0.005 (HA) is accepted. 120 respondents 70 respondents (58.3%) high, 43 respondents (35.8%) moderate, and 7 respondents (5.8%) haveself efficacy andself esteem markp value 0.000<0.005 (HA) is accepted.